Hydrology Modulates the Microplastics Composition and Transport Flux Across the River–Sea Interface in Zhanjiang Bay, China - Xiaoqing Chen; Peng Zhang; Jing Lu; Yuanting Chen; Jibiao Zhang (Journal of Marine Science and Engineering)
Estuaries act as significant pathways for plastic waste entry into the oceans, with microplastics (MPs) being intricately influenced by river and coastal hydrodynamics. MPs become entrapped within estuaries during transport, particularly at the river–sea interface, which impacted by tidal fluctuations. However, few studies have examined the role of the impacts of tidal variations on microplastic abundance and export flux at the river–sea interface across contrasting hydrological regimes (dry vs. wet seasons). In this study, we conducted observations to assess MPs abundance, composition, and flux in the Suixi Estuary of Zhanjiang Bay, China The results indicated an overall mean abundance of MPs of 91.1 ± 75.0 items/L, which was linked to tidal variations, decreasing during high tides and increasing during low tides. Transparent color, fibrous shape, and a size range of 100–330 μm were the most prevalent characteristics in water samples. MPs diversity was higher during the wet season compared to the dry season. In addition, the MPs influx was about 1.61 × 109 items/year from the river to the sea across both seasons. Additionally, hydrological regimes, tidal forces, and human activities were identified to influence MPs abundance and flux. This quantitative analysis establishes a mechanistic framework for understanding hydrological impacts on estuarine MPs transport, providing critical baseline data for developing targeted pollution management strategies in coastal ecosystems.